Pt–Re–Ge/Al2O3 catalysts for n-octane reforming: Influence of the order of - Carvalho, Luciene (2012)
Trimetallic Pt–Re–Ge supported catalysts for naphtha reforming were prepared by successive impregnation of suitable precursors on gamma alumina. The order of addition of these precursors was varied and its influence on the catalytic properties was assessed by means of the model reaction of n-octane reforming. It was found that the order of addition of the metal precursors greatly affects the performance and properties of these systems, which in turn is closely related to the first impregnated metal. When platinum is impregnated before rhenium and germanium the metals are reduced separately resulting in catalysts with high dehydrogenation activity and low hydrogenolysis activity. On the other hand, the impregnation of germanium before the other metals leads to the production of catalysts with low activities for dehydrogenation and high activity for hydrogenolysis, as a consequence of the strong interactions among the metals. By adding rhenium before the other metals, catalysts with intermediate behavior are produced. For all catalysts, platinum interacts more strongly with rhenium than with germanium. The order of addition does not modify the acidic properties of the support but germanium and rhenium seem to change the acidity of the support in the vicinity of the metals, causing differences in the selectivity to aromatic compounds and paraffinic isomers. These features can be used to tailor catalysts with high selectivity for the production of aromatics or isoparaffins, depending on the purpose of the reforming process. The RePtGe catalyst has the highest selectivity to branched isoparaffins and then can be used to produce isoparaffins-rich gasoline while a reformate rich in aromatics can be obtained by using the GeRePt catalyst.